Physicochemical, microbiological, and sensory properties of almond milk yogurt-like products with varied concentrations of tapioca starch as stabilizer - Zainuddin, Nurazlin; Khalid, Nurul Izzah; Mohsin, Aliah Zannierah; Mohamad Azman, Ezzat; Mahmud @ Ab Rashid, Nor Khaizura; Abd Rahim, Muhamad Hafiz (Hibiscus Publisher Enterprise, 2024)
This study investigates the impact of tapioca starch concentrations on almond milk yoghurt-like products, aiming to enhance their physicochemical and sensory properties. Almond milk with varying tapioca starch levels (0%, 1%, 2%, 3%) underwent pasteurization, and development into yoghurt. The findings indicated that, among the variables examined, tapioca starch emerged as a significant factor influencing specific physicochemical properties, notably viscosity, whereas the fermentation period demonstrated less notable impact. While commercial dairy yoghurt exhibited superior texture attributes, tapioca starch did not significantly affect color or lactic acid bacteria viability. Almond milk yoghurt-like products with 3% tapioca starch showed improved texture but still lagged behind commercial dairy yoghurt in overall sensory acceptance. The study suggests further development is necessary to enhance almond milk yoghurt-like products' consumer acceptability.